DEVELOPMENT OF DIGITAL PLATFORMS AND PLATFORM - Rakhim Rajabbayevich Matniyazov (Ecominds Press, 2025)
The development of digital platforms has revolutionized the global economy, creating new business models and transforming traditional industries. Platform-based economies leverage digital technologies to connect users, businesses, and service providers, facilitating seamless transactions and interactions. In Uzbekistan, the expansion of digital platforms is driving economic modernization, fostering entrepreneurship, and improving service delivery in various sectors, including finance, commerce, and transportation. This study explores the role of digital platforms in shaping the platform economy, highlighting their impact on economic growth, innovation, and market competition. It examines the challenges associated with digital platform development, such as regulatory concerns, digital infrastructure limitations, and cybersecurity risks. By analyzing international best practices and their relevance to Uzbekistan, this research provides insights into the strategic measures required to enhance platform-based economic activities. The findings emphasize the need for policy reforms, investment in digital infrastructure, and skills development to maximize the benefits of digital platforms in Uzbekistan’s evolving economy.
Keywords: Digital platforms, platform economy, digital transformation, online marketplaces, e-commerce, financial technology, innovation, Uzbekistan, economic growth, digital infrastructure.